What was it Like? - Hunt, Roderick and Brychta, Alex (China Oxford University Press, 2003)
Presents a reading scheme that contains stories, meant for children. This title offers teaching support material - guided reading cards, and teacher's notes included free with each pack of "Oxford Reading Tree" books. It contains "Take-Home" cards for every storybook from Stages 1 - 9, and has a website with downloadable photocopy masters.
Include Color Illustrations
Keywords: a